Shari'ah perspective ratio of islamic financing: Base profit rate vs rule 78 - Halim N.A.; Gazali N.; Ahmad W.M.A.W.; Mamat M. (Blue Eyes Intelligence Engineering and Sciences Publication, 2024)
Indexed by Scopus